Method for improving crystallinity of polyamide and polyamide composite material
By combining metal chloride and polyhydroxy compounds in polyamide materials and combining appropriate light absorbers, the problem of existing materials maintaining processing performance while high infrared transmittance and barriers visible and ultraviolet light is solved. The material is efficient infrared transparency and good mechanical properties.
Patent Information
- Application Number
- CN202411515788.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-26
- Publication Date
- 2025-02-07
AI Technical Summary
It is difficult for existing infrared penetration plastic materials to achieve high infrared transmittance and block visible and ultraviolet light while ensuring processing performance.
The infrared permeability and fluidity of the polyamide material are improved by combining metal chlorides with polyhydroxy compounds such as pentaerythritol, dipentaerythritol and polypentaerythritol, and synergistically combining visible light absorbers and ultraviolet absorbers.
The polyamide composite material has a high infrared transmittance and blocks visible and ultraviolet light at the same time. The material is not brittle, has good impact resistance, good fluidity, and has good toughness and processing properties.
Smart Images

Figure CN119391173A_ABST
Abstract
Description
[0001] This application is a division of the invention patent with application number 2024102054828 and application date February 26, 2024. Technical Field
[0002] The invention belongs to the field of modified polyamide materials, in particular to a method for improving the crystallinity of polyamide. Background Art
[0003] Infrared penetrating plastics are also called infrared transmission plastics. The characteristic of this material is that it gives black vision in the visible light range (400-700nm visible light transmittance is less than 1%), but can transmit the near-infrared region with a wavelength of 800-1600nm or more. The infrared transmittance can range from 80% to 93% depending on the thickness of the component, the working band and the color requirements. Infrared penetrating plastics can be used in infrared communications, infrared photography, infrared night vision, infrared navigation, infrared welding, infrared thermal energy regulation and other fields.
[0004] Most of the known infrared light-transmitting plastics are black, purple or dark red materials formed by modifying PC, PMMA, GPPS resins. Among various polymer materials, polyamide is a very important type of engineering plastics, which has excellent mechanical properties, thermal properties, and corrosion resistance. It has a very wide range of applications, involving various industries such as industrial manufacturing, agricultural production, machinery manufacturing, electronic appliances, and automobile manufacturing. If an infrared light-transmitting polyamide composite material can be provided, which allows infrared light to pass through but cuts off visible light and ultraviolet light, it will greatly broaden the application field of polyamide and provide more and better choices for infrared light-transmitting plastics used in infrared communications, infrared photography, infrared night vision, infrared navigation, infrared welding, and infrared thermal energy regulation equipment. Summary of the invention
[0005] The purpose of the present invention is to provide a method for improving the crystallinity of polyamide and a polyamide composite material, wherein the MFR value increases while the crystallization temperature of the polyamide composite material is increased, and the polyhydroxy compound helps to improve the melt fluidity of the polyamide composite material.
[0006] The present invention also provides an infrared light-transmitting polyamide composite material, which has a high infrared light transmittance while ensuring good processing performance, and can cut off visible light and ultraviolet light.
[0007] The invention also provides a method for preparing an infrared light-transmitting polyamide composite material and application of the composite material in injection-molded products, especially in infrared photographic equipment or infrared communication equipment.
[0008] According to a first aspect of the present invention, a method for improving the crystallinity of polyamide comprises: uniformly mixing raw materials including polyamide and a nucleating agent, and extruding the raw materials using an extruder; wherein the nucleating agent comprises a polyhydroxy compound, and the polyhydroxy compound comprises a combination of one or more of pentaerythritol, dipentaerythritol and polypentaerythritol.
[0009] In one embodiment, the weight percentage of the polyhydroxy compound is 0.2-1.0%.
[0010] In one embodiment, the weight percentage of the polyhydroxy compound is 0.1-0.3%.
[0011] In one embodiment, the polyhydroxy compound is pentaerythritol.
[0012] In one embodiment, the nucleating agent consists of the polyhydroxy compound.
[0013] In one embodiment, the raw material does not include a lubricant.
[0014] In one embodiment, the polyamide is selected from polyamide 6 or its copolymer, polyamide 66, polyamide 56, polyamide 610, and polyamide 612.
[0015] In one embodiment, the raw material further includes metal chloride, and the metal chloride is selected from a combination of one or more of calcium chloride, lithium chloride, aluminum chloride and lanthanum chloride, and the weight percentage of the metal chloride and the nucleating agent in the raw material is 0.5-5%.
[0016] In one embodiment, the weight percentage of the metal chloride and the nucleating agent in the raw material is 1.2-3.6%.
[0017] In one embodiment, the raw material further comprises a visible light absorber, an ultraviolet absorber and an ultraviolet absorption synergist, the weight percentage of the visible light absorber and the ultraviolet absorber in the raw material is 0.1-1.0% respectively, and the weight percentage of the ultraviolet absorption synergist in the raw material is 0.05-0.5%.
[0018] In one embodiment, the raw material further includes an acid binder, the weight percentage of the acid binder is 0.1-1%, and the acid binder is selected from a combination of one or more of calcium stearate, sodium stearate, barium stearate or zinc stearate.
[0019] According to another aspect of the present invention, a polyamide composite material, wherein the raw materials thereof include polyamide, a visible light absorber, an ultraviolet absorber and a light transmittance enhancer, in terms of weight percentage; wherein the weight percentages of the visible light absorber and the ultraviolet absorber in the raw materials are 0.1 to 1.0%, respectively; the weight percentage of the light transmittance enhancer in the raw materials is 1 to 5%, and the light transmittance enhancer includes a metal chloride and a polyhydroxy compound, and the polyhydroxy compound includes a combination of one or more of pentaerythritol, dipentaerythritol and polypentaerythritol.
[0020] In a preferred embodiment, the chloride is selected from one or more combinations of calcium chloride, lithium chloride, aluminum chloride and lanthanum chloride.
[0021] The weight percentage of the optical transmittance enhancer is any value between 1% and 5%; for example, the weight percentage of the optical transmittance enhancer can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. In a preferred embodiment, the weight percentage of the optical transmittance enhancer is 1.2 to 3.6%. More preferably, the weight percentage of the optical transmittance enhancer is 1.5 to 3%.
[0022] In a preferred embodiment, the ratio of the metal chloride to the polyhydroxy compound is 1:0.3-0.5.
[0023] In a preferred embodiment, the visible light absorber includes aniline black.
[0024] In a preferred embodiment, the weight percentage of the visible light absorber in the raw material is 0.1-1.0%. For example, the weight percentage of the visible light absorber is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%. More preferably, the weight percentage of the visible light absorber in the raw material is 0.1-0.5%; further 0.1-0.3%.
[0025] In a preferred embodiment, the weight percentage of the ultraviolet absorber in the raw material is 0.1-1.0%. For example, the weight percentage of the ultraviolet absorber is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%. More preferably, the weight percentage of the ultraviolet absorber in the raw material is 0.1-0.5%; further 0.1-0.3%.
[0026] In a preferred embodiment, the ultraviolet absorber is selected from 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (ultraviolet absorber UV-P), 2,4-dihydroxybenzophenone (ultraviolet absorber UV-0 (BP-1)), 2-hydroxy-4-methoxybenzophenone (ultraviolet absorber UV-9), 2-hydroxy-4-n-octyloxybenzophenone (ultraviolet absorber UV-531), 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole (ultraviolet absorber UV-327), 2-cyano-3,3-diphenylacrylate (octocrylene, N-539), hexamethylphosphoric acid triamide (violet light inhibitor, light stabilizer HPT), 2-(2-hydroxy-3',5'-dicumylphenyl)-benzotriazole (ultraviolet absorber UV-234) and one or more combinations thereof.
[0027] In a preferred embodiment, the raw material further comprises an ultraviolet absorption synergist. In a preferred embodiment, the weight percentage of the ultraviolet absorption synergist in the raw material is 0.05-0.5%; for example, it can be 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4% or 0.5%. More preferably, the weight percentage of the ultraviolet absorption synergist in the raw material is 0.1-0.3%.
[0028] In a preferred embodiment, the UV absorption synergist is selected from a combination of one or more of 4-benzoyloxy-2,2,6,6-tetramethylpiperidine (light stabilizer 744), tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite (light stabilizer GW-540), poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-S-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino] (light stabilizer 944) and bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate (light stabilizer 770).
[0029] In a preferred embodiment, the raw material further comprises an acid binding agent. More preferably, the weight percentage of the acid binding agent is 0.1-1%; for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%. Further, the weight percentage of the acid binding agent is 0.3-0.8%.
[0030] More preferably, the acid binding agent is selected from one or more combinations of calcium stearate, sodium stearate, barium stearate or zinc stearate.
[0031] In a preferred embodiment, the raw material does not include a lubricant and / or a nucleating agent.
[0032] In a preferred embodiment, the weight percentage of the polyamide in the raw material is greater than 93%.
[0033] In a preferred embodiment, the polyamide is selected from polyamide 6 or its copolymer, polyamide 66, polyamide 56, polyamide 610, and polyamide 612.
[0034] According to the second invention of the present invention, a method for preparing the polyamide composite material comprises: weighing raw materials according to a proportion, mixing them evenly, and extruding them to obtain polyamide composite material particles.
[0035] According to a third aspect of the present invention, a use of the polyamide composite material in an injection molded product.
[0036] In a preferred embodiment, the injection molded product includes an accessory of infrared photographic equipment or infrared communication equipment, or an infrared receiving window.
[0037] According to another aspect of the present invention, the polyamide composite material is used in a sheet material. The polyamide composite material is extruded into a sheet material by an extruder.
[0038] In a preferred embodiment, the thickness of the sheet is 0.2-0.6 mm, more preferably 0.4±0.1 mm.
[0039] The mechanism of the present invention is: if only metal chloride is used, metal ions and amide groups are combined through coordination bonds, and the bond energy is between covalent bonds and hydrogen bonds. Compared with hydrogen bonds, higher energy needs to be given to destroy the coordination bonds. Therefore, only metal chloride is used to improve the light transmittance of polyamide. During melt processing, a large number of covalent bonds exist to limit the movement of polyamide segments. As the amount of chloride increases, the coordination bond density increases, and the fluidity of polyamide deteriorates when melted. However, when a metal chloride and a polyhydroxy small molecule compound are compounded, part of the hydrogen bonds replace the coordination bonds. During melt processing, the hydrogen bonds are more easily destroyed, releasing part of the polyamide segments that are restricted from moving. At the same time, the polyhydroxy compound can also act as an internal lubricant, thereby achieving the purpose of improving the fluidity of the polymer.
[0040] On the other hand, when only metal chloride is used as a permeability enhancer, the movement of polyamide chain segments is more easily restricted, stress relaxation is slowed down, and during injection molding, the stress inside the product is relatively large, and the impact resistance of the material, especially the dry impact resistance, is reduced. The introduction of polyhydroxy small molecule compounds, due to their greater degree of freedom, can easily reach dynamic equilibrium in a shorter time during stress relaxation, thereby helping to improve the impact resistance of the material.
[0041] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0042] The polyamide composite material of the present invention is prepared by compounding metal chloride, a polyhydroxy compound selected from pentaerythritol, dipentaerythritol and polypentaerythritol, and an ultraviolet absorber, etc., which cooperate with each other to make the composite material have a higher infrared transmittance, can block visible light and ultraviolet rays, and at the same time maintain the better processing performance of polyamide. The obtained polyamide composite material is not brittle, has good impact resistance, good fluidity, good toughness and processing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0044] Figure 1 This is the DSC graph of the polyamide composite material of Example 1.
[0045] Figure 2 This is the DSC graph of the polyamide composite material of Example 3.
[0046] Figure 3 This is the DSC graph of the polyamide composite material of Example 5.
[0047] Figure 4 This is the DSC graph of the polyamide composite material of Comparative Example 1. DETAILED DESCRIPTION
[0048] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0049] The inventors have found through experiments that adding metal chloride to polyamide can improve the infrared transmittance of polyamide. However, the addition of metal chloride also causes the fluidity of the polyamide material to deteriorate, and the obtained polyamide composite material is brittle and has poor impact resistance. The material is brittle and easy to crack in the dry state. Based on this, the inventors have further studied and found that when metal chloride is compounded with a polyhydroxy compound selected from pentaerythritol, dipentaerythritol and polypentaerythritol, the infrared transmittance of the polyamide material can be improved, and the defects of brittleness and poor processability of the material can be overcome. The polyamide composite material of the present application is prepared by compounding metal chloride and a polyhydroxy compound selected from pentaerythritol, dipentaerythritol and polypentaerythritol into polyamide, and then coordinating with a visible light absorber and an ultraviolet light absorber. Pentaerythritol, dipentaerythritol and polypentaerythritol destroy the hydrogen bonds of polyamide at high temperatures to increase the fluidity of the material, and exist stably at low temperatures to play a role similar to that of a nucleating agent. The crystallization of the material is finer and the toughness is better. The polyamide composite material has a higher infrared light transmittance and can block visible light and ultraviolet light. At the same time, the material is not brittle and has better toughness and processing performance.
[0050] The present application relates to a polyamide composite material capable of transmitting infrared light, wherein the raw materials thereof include, by weight percentage:
[0051] Polyamide 90-98%;
[0052] Visible light absorber 0.1~1.0%;
[0053] Ultraviolet absorber 0.1~1.0%;
[0054] Light transmittance enhancer 0.5-5%;
[0055] UV absorption synergist 0.05-0.5%;
[0056] Others are processing aids.
[0057] Among them, the polyamide can be selected from a combination of one or more of polyamide 6 or its copolymer, polyamide 66, polyamide 56, polyamide 610, and polyamide 612. The visible light absorber includes aniline black. The ultraviolet absorber is selected from a combination of one or more of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-3', 5'-di-tert-phenyl)-5-chlorobenzotriazole, 2-cyano-3,3-diphenylacrylate, hexamethylphosphoric triamide, and 2-(2-hydroxy-3', 5'-dicumylphenyl)-benzotriazole. 2-(2ˊ-Hydroxy-5ˊ-methylphenyl)benzotriazole (UV absorber UV-P) can absorb ultraviolet rays with a wavelength of 270 to 380 nm; 2,4-dihydroxybenzophenone (UV absorber UV-O) has a maximum absorption wavelength range of 280 to 340 nm; 2-hydroxy-4-methoxybenzophenone (UV absorber UV-9) has a maximum absorption wavelength range of 280 to 340 nm; 2-hydroxy-4-n-octyloxybenzophenone (UV absorber UV-53 1), strongly absorbs ultraviolet light with a wavelength of 240 to 340 nm; 2-(2'-hydroxy-3', 5'-di-tert-phenyl)-5-chlorobenzotriazole (ultraviolet absorber UVP-327), strongly absorbs ultraviolet light with a wavelength of 270 to 380 nm; 2-cyano-3,3-diphenylacrylate isooctyl ester, with a maximum absorption wavelength range of 290 to 400 nm; hexamethylphosphoric acid triamide (light stabilizer HPT), can effectively absorb ultraviolet light with a wavelength of 270-380 nanometers. The ultraviolet absorption synergist is selected from one or more of 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite, poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-S-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino] and bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate. Among them, 4-benzoyloxy-2,2,6,6-tetramethylpiperidine (light stabilizer 744), when used together with an antioxidant and an ultraviolet absorber, has an excellent synergistic effect.
[0058] The light transmittance enhancer includes metal chloride and polyhydroxy compound; the metal chloride is selected from one or more combinations of calcium chloride, lithium chloride, aluminum chloride and lanthanum chloride; the polyhydroxy compound includes one or more combinations of pentaerythritol, dipentaerythritol and polypentaerythritol.
[0059] The processing aid comprises an acid binding agent, the weight percentage of the acid binding agent is 0.1-1%, and the acid binding agent is selected from a combination of one or more of calcium stearate, sodium stearate, barium stearate or zinc stearate.
[0060] The processing aids also include one or more combinations of plasticizers, lubricants, mold release agents, nucleating agents, antioxidants, and fillers.
[0061] In some preferred embodiments, the processing aid does not include a lubricant, and the polyol compound acts as a lubricant. The specific formula is: polyamide 90-98%; visible light absorber 0.1-1.0%; ultraviolet absorber 0.1-1.0%; light transmittance enhancer 0.5-5%; ultraviolet absorption synergist 0.05-0.5%; the others are processing aids, and the processing aids do not include lubricants. Further, the processing aids include acid binding agents; the processing aids also include a combination of one or more of nucleating agents, plasticizers, mold release agents, antioxidants, and fillers.
[0062] In other preferred embodiments, the processing aid does not include a nucleating agent, and the polyol compound acts as a nucleating agent. The specific formula is: polyamide 90-98%; visible light absorber 0.1-1.0%; ultraviolet absorber 0.1-1.0%; light transmittance enhancer 0.5-5%; ultraviolet absorption synergist 0.05-0.5%; the others are processing aids, and the processing aids do not include a nucleating agent. Further, the processing aid includes an acid-binding agent; the processing aid also includes a combination of one or more of a lubricant, a plasticizer, a release agent, an antioxidant, and a filler.
[0063] In some other preferred embodiments, the processing aid does not include lubricants and nucleating agents, and the polyol compound acts as both a lubricant and a nucleating agent. The specific formula is: 90-98% polyamide; 0.1-1.0% visible light absorber; 0.1-1.0% ultraviolet absorber; 0.5-5% light transmittance enhancer; 0.05-0.5% ultraviolet absorption synergist; the others are processing aids, and the processing aids do not include lubricants and nucleating agents. Further, the processing aids include acid binding agents; the processing aids also include a combination of one or more of plasticizers, release agents, antioxidants, and fillers.
[0064] The above components are mixed evenly in proportion and granulated by a twin-screw extruder. The temperature of the twin-screw extruder is 120°C, 180°C, 220°C, 240°C, 240°C, 240°C, 240°C, 240°C, 240°C, 235°C from the first zone to the eleventh zone, and the die temperature is 235°C; the main screw speed is 300 rpm. When used, products can be injection molded, and the injection molding temperature of the test sample is 235°C, 255°C, 255°C, 255°C from the first zone to the fourth zone.
[0065] The polyamide composite material can also be formed into a sheet by an extruder, and the thickness of the sheet is 0.2-0.6 mm, and more preferably 0.4±0.1 mm.
[0066] As a sheet material, the formula of the polyamide composite material may also be preferably as follows: polyamide 90-98%;
[0067] Visible light absorber 0.1~1.5%;
[0068] Ultraviolet absorber 0.1~1.5%;
[0069] Light transmittance enhancer 0.5-5%;
[0070] UV absorption synergist 0.05-0.5%;
[0071] Others are processing aids.
[0072] The selection of specific ingredients is the same as above.
[0073] The raw materials used in the following examples and comparative examples are shown in Table 1.
[0074] Table 1 Raw materials and their sources
[0075] raw materials supplier Polyamide 6 (Nylon 6) Jiangsu Yongtong New Materials Technology Co., Ltd. <![CDATA[CaCl2]]> Weifang Dakang Chemical Co., Ltd. Pentaerythritol Yuntianhua Group Co., Ltd. Dipentaerythritol Yuntianhua Group Co., Ltd. Aniline Black S Shenyang Huaxi Biotechnology Co., Ltd. UV absorber UV-P Jiangsu Bosite Chemical Technology Co., Ltd. Light Stabilizer 944 Tianjin Lianlong New Materials Co., Ltd. Triacetin Shandong Polychemical Co., Ltd. EBS Changzhou Kesai Chenggong Plastic Material Co., Ltd. <![CDATA[CaSt2]]> Anhui Shafeng New Materials Co., Ltd. PETS Jiaxing Zhongcheng Environmental Protection Technology Co., Ltd. MMT Zhejiang Fenghong New Materials Co., Ltd. P22 Brüggemann (Germany) AO1098 Tianjin Lianlong New Materials Co., Ltd. Pigment Carbon Black Tianjin Jindadi Chemical Co., Ltd. <![CDATA[TiO2]]> Bamon Industrial (Shanghai) Co., Ltd. <![CDATA[BaSO4]]> Shandong Borida Radiation Protection Engineering Co., Ltd.
[0076] Performance testing method:
[0077] The tensile test was carried out according to ASTM-D638 standard. The bending test was carried out according to ASTM-D790 standard.
[0078] Notched impact is tested according to ASTM-D256 standard.
[0079] Light transmittance: tested according to ASTM D1003 standard.
[0080] The melt index is tested according to ASTM D1238 standard, with a test temperature of 260°C and a load of 2.16 kg.
[0081] The DSC (thermal analysis) crystallization temperature test method is: the sample is heated from room temperature to 260°C at a rate of 10°C / min, kept constant for 2 minutes, and then cooled to room temperature at a rate of 10°C / min. The peak value of the cooling crystallization peak is defined as the crystallization temperature.
[0082] Examples 1 to 5 and Comparative Examples 1 to 3
[0083] The raw materials were weighed according to Table 2, mixed evenly, and extruded and granulated using a screw extruder to obtain the polyamide composite materials of Examples 1 to 5. The performance test results are shown in Table 2 below. Among them, Figures 1 to 4The DSC graphs of Examples 1, 3, 5 and Comparative Example 1 are shown in sequence, and the crystallization temperatures are shown in Table 2 below. The materials of Comparative Examples 1 to 3 are made into color plates with a thickness of 1 mm, and the transmittances of light of different wavelength bands are shown in Table 2 below.
[0084] Table 2 Examples 1 to 5 and Comparative Examples 1 to 3
[0085]
[0086]
[0087] As can be seen from Table 2, as the amount of the polyol added increases, the crystallization temperature of the polyamide composite material decreases and the MFR value increases, and the polyol helps to improve the melt fluidity of the polyamide composite material. The crystallization temperature of the pure polyamide material without pentaerythritol is significantly lower than that of Examples 1, 3 and 5, and the MFR value is also lower than that of Examples 1 to 5.
[0088] Depend on Figures 1 to 4 It can be seen from the DSC thermal analysis diagram that the above polyols (such as pentaerythritol) can also act as nucleating agents. Therefore, in the formula of the above embodiment, the polyols (such as pentaerythritol) exist as lubricants and nucleating agents at the same time. In addition, the applicant also conducted DSC thermal analysis on the composite materials after PA6 and several nucleating agents were compounded, and the results are compared as follows:
[0089] PA6+pentaerythritol: The crystallization peak temperatures are 191.3°C, 190.4°C and 189.6°C, respectively, and the amounts of pentaerythritol added are 0.2wt%, 0.6wt% and 1.0wt% respectively;
[0090] PA6+0.2wt% P22: crystallization peak temperature is 193.0℃;
[0091] PA6+0.3wt%MMT: crystallization peak temperature is 192.4℃;
[0092] PA6+0.15wt%MMT+0.05wt%P22: the crystallization peak temperature is 191.6°C.
[0093] The ideal dosage of the polyhydroxy compound (such as pentaerythritol) for the nucleation effect of polyamide is between 0.1 and 0.3 wt%. If the dosage increases, the crystallization peak temperature moves toward the low temperature direction, the crystallization peak becomes wider, and the tailing phenomenon becomes more serious.
[0094] Embodiments 6 to 16
[0095] The raw materials were weighed according to Table 3, mixed evenly, extruded by a screw extruder, and granulated to obtain the polyamide composite materials of Examples 6 to 16. The performance test results are shown in Table 3 below. The composite materials of Examples 6 to 16 were made into color plates with a thickness of 1 mm, and the transmittance of light in different bands was shown in Table 3 below.
[0096] Table 3
[0097]
[0098] Comparative Examples 4-5
[0099] The raw materials were weighed according to Table 4, mixed evenly, extruded by a screw extruder, and granulated to obtain the polyamide composite materials of Comparative Examples 4 and 5. The performance test results are shown in Table 4 below. The composite materials of Comparative Examples 4 and 5 were made into color plates with a thickness of 1 mm, and the transmittance of light in different bands was shown in Table 4 below.
[0100] Table 4
[0101] Comparative Example 4 Comparative Example 5 PA6 93.8 93.8 Pentaerythritol -- -- UV absorber UV-P -- -- Light Stabilizer 944 -- -- Aniline Black S -- -- <![CDATA[CaCl2]]> 2.5 2.5 Triacetin -- -- EBS 1 1 <![CDATA[CaSt2]]> 0.5 0.5 MMT -- -- P22 -- -- AO1098 0.2 0.2 Pigment Carbon Black -- -- <![CDATA[TiO2]]> 2 -- <![CDATA[BaSO4]]> -- 2 MFR(g / 10min) 12.13 12.68 UV light transmittance (%) 0.0 0.0 Visible light transmittance (%) 3.7 0.0 Infrared light transmittance (%) 3.7 0.0
[0102] In Table 3 and Table 4, triacetin is used as a plasticizer and internal lubricant. If the amount used is too large, there is a risk of precipitation, thereby contaminating adjacent optical components. EBS is ethylene stearate, which is used as an internal and external lubricant. CaSt2 is calcium stearate, which also has the functions of external lubricant, release agent and acid binding agent. P22 is nylon 22, which is used as an organic nucleating agent; MMT is modified montmorillonite, which is used as an inorganic nucleating agent; the combination of the two nucleating agents can adjust the proportion of different types of unit cells, thereby balancing strength or rigidity and toughness. AO1098 is antioxidant 1098. Pigment carbon black is used as a filler, and it can also give black color to block the transmission of light. TiO2 is titanium dioxide, and BaSO4 is barium sulfate, both of which are used to block the transmission of light.
[0103] Combining Table 3 and Table 4, it can be seen that the polyamide composite materials of Examples 6 to 16 have higher infrared light transmittance and / or higher MFR value than the comparative examples. Among them, the composite materials of Examples 10 to 13, 15 and 16 also have excellent barrier properties for ultraviolet light and visible light, while at the same time, they still maintain an infrared light transmittance greater than 30% and a higher MFR value, which are better than Comparative Examples 4 and 5.
[0104] As shown in this specification and claims, the terms "comprises" and "include" only indicate the inclusion of the steps and elements that have been clearly identified, and these steps and elements do not constitute an exclusive list, and the method or device may also include other steps or elements. The term "and / or" as used herein includes any combination of one or more of the relevant listed items.
[0105] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0106] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art. If there is any conflict or inconsistency between the definitions used herein and the definitions contained in other public documents, the definitions used herein shall prevail.
[0107] The above embodiment is only for illustrating the technical concept and features of the present invention, and is a preferred embodiment. Its purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the crystallinity of polyamide, characterized in that: include: The raw materials including polyamide and nucleating agent are mixed uniformly and extruded by an extruder; wherein the nucleating agent includes a polyhydroxy compound, and the polyhydroxy compound includes a combination of one or more of pentaerythritol, dipentaerythritol and polypentaerythritol.
2. The method for improving the crystallinity of polyamide according to claim 1, characterized in that: The weight percentage of the polyhydroxy compound is 0.2-1.0%.
3. The method for improving the crystallinity of polyamide according to claim 1, characterized in that: The weight percentage of the polyhydroxy compound is 0.1-0.3%.
4. The method for improving the crystallinity of polyamide according to any one of claims 1 to 3, characterized in that: The polyhydroxy compound is pentaerythritol.
5. The method for improving the crystallinity of polyamide according to any one of claims 1 to 3, characterized in that: The nucleating agent consists of the polyhydroxy compound.
6. The method for improving the crystallinity of polyamide according to any one of claims 1 to 3, characterized in that: The polyamide is selected from one of polyamide 6 or its copolymer, polyamide 66, polyamide 56, polyamide 610 and polyamide 612.
7. The method for improving the crystallinity of polyamide according to any one of claims 1 to 3, characterized in that: The raw material further comprises metal chloride, which is selected from one or more combinations of calcium chloride, lithium chloride, aluminum chloride and lanthanum chloride. The weight percentage of the metal chloride and the nucleating agent in the raw material is 0.5-5%.
8. The method for improving the crystallinity of polyamide according to claim 7, characterized in that: The weight percentage of the metal chloride and the nucleating agent in the raw material is 1.2-3.6%.
9. The method for improving the crystallinity of polyamide according to any one of claims 1 to 3, characterized in that: The raw materials further include a visible light absorber, an ultraviolet absorber and an ultraviolet absorption synergist, wherein the weight percentages of the visible light absorber and the ultraviolet absorber in the raw materials are 0.1 to 1.0% respectively, and the weight percentage of the ultraviolet absorption synergist in the raw materials is 0.05 to 0.5%; The raw materials also include an acid binding agent, the weight percentage of the acid binding agent is 0.1-1%, and the acid binding agent is selected from a combination of one or more of calcium stearate, sodium stearate, barium stearate or zinc stearate; The feedstock does not include lubricants.
10. A polyamide composite material, characterized in that: The polyamide composite material is prepared by the method for improving the crystallinity of polyamide according to any one of claims 1 to 9.